Evaluation of an interprofessional education intervention in partnership with patient educators: Interprofessional Education with Patients - Ferri, Paola; Vivarelli, Chiara; Lui, Fausta; Alberti, Sara; Rovesti, Sergio; Serafini, Alice; Di Lorenzo, Rosaria; Amati, Gabriele; Padula, Maria Stella (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Patient involvement in interprofessional education is a novel approach to building collaborative and empathic skills in students. However, this area of teaching is lacking in rigorous studies. The project aimed to evaluate whether an interprofessional education intervention in partnership with patient educators (IPE-PE) would increase readiness for interprofessional learning and empathy in health sciences students. Methods: This is the report of a didactic innovation project. Participants included 310 undergraduate health sciences students who took part in an IPE-PE intervention. Data were collected before and after the training, using the Readiness for Interprofessional Learning Scale (RIPLS) and the Jefferson Scale of Empathy-Health Professions Student version (JSE-HPS). Only at the end of the intervention, a data collection form was administered to explore the value of the patient educator in the training and to investigate the socio-demographic variables. Results: The mean age of participants was 21±3.2 SD years and 76% were female. A paired t-test showed significant changes from before to after the IPE-PE in the mean total RIPLS score (42.7±5.8 SD vs 44.62±5.9 SD, P<0.001) and the mean total JSE-HPS score (112.7±12.5 SD vs 116.03±12.8 SD, P<0.001). Conclusions: Our students reported that IPE-PE had helped them to become more effective healthcare team members, to think positively about other professionals, and to gain empathic understanding of the perspective of the person being cared for. The results of the project confirm that the intervention promoted the development of empathy, fostering a better understanding of the patient-centred perspective.